MODELING ORGANIZATION CLIENTS BEHAVIOR - M. K. Bouza; V. S. Gorshunov (Informatika)
A system of modeling organization clients behavior is proposed and studied, as well as its functional and architectural solutions. A client identification mechanism based on control and dynamic parameters of a given objective function is proposed.